Profil Mahasiswa Pendidikan Masyarakat Yang Berwirausaha: Karakteristik, Latar Belakang, Management Waktu, Kemajuan Usaha - Hendra Yuda Pratama; Yus Darusman; Adang Danial (Ikatan Mahasiswa Pendidikan Luar Sekolah ( IMADIKLUS ), 2022)
The research in this thesis is backed by the phenomenon of many new entrepreneurship community education students but the business does not last long because it experiences various problems and eventually goes bankrupt. In general, students who are new entrepreneurship do not have qualified entrepreneurial skills because they only follow trends and friends so they can not know the right strategies and steps in making business decisions. They are only able to survive the business for a maximum of 5 months after that they change businesses and even go bankrupt. In the midst of the crisis of experience and expertise of entrepreneurship students there are 7 community education students who managed to open a business even able to develop their business and open new jobs.Based on the above, researchers are interested in conducting research on 7 students who succeeded in their efforts. The title of this study is the Profile of Entrepreneurship Community Education Students. The formulation of the problem in this study is How to Profile Entrepreneurship Community Education Students.This study uses qualitative methods by selecting 7 sources who have and manage the business for more than one year and are considered successful in their entrepreneurship. Data collected using instruments in the form of Observation and Documentation and In-depth interviews with informants. The data is qualitatively analyzed.The results of this study showed that the Profile of Entrepreneurship Community Education Students is influenced by family, education, environment, motivation and work history. So as to produce a profile of students who are resilient, creative, innovative, confident, visionary, open to new things and Optimistic. This characteristic is what supports the success of 7 community education students in entrepreneurship.The conclusion of this study is that students decide to become entrepreneurs because of the influence of internal and external factors. On the external factors, there is the influence of the educational environment, family, friends, opportunities and work history. External factors affect internal factors, and vice versa. These two factors influence each other.